2023
DOI: 10.3390/hydrology10040088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Time Period Length on the Determination of Long-Term Mean Annual Discharge

Abstract: Currently, the 40-year-long reference period 1961–2000 is used in Slovakia for systematic assessment of the hydrological regime. The World Meteorological Organization recommends unifying the climatic normal 1991–2020 with a reference period for hydrological characteristics for the purpose of climate change research. We have analyzed changes in the long-term mean annual discharges at 113 water-gauging stations over different time periods. Considering the history of the reference periods used in Slovakia, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The results in Poórová et al (2023) indicated as well, that the use of the 30-year long period 1991-2020 is probably suitable, especially for mutual comparison between climatic and hydrological characteristics for climate change research. The period 1991-2020 is the one recommended by WMO as the reference period for current assessment of hydrological situation, to be comparable with climatic assessment based on the same reference period.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The results in Poórová et al (2023) indicated as well, that the use of the 30-year long period 1991-2020 is probably suitable, especially for mutual comparison between climatic and hydrological characteristics for climate change research. The period 1991-2020 is the one recommended by WMO as the reference period for current assessment of hydrological situation, to be comparable with climatic assessment based on the same reference period.…”
Section: Discussionmentioning
confidence: 83%
“…In the water management of Slovakia, the reference period 1961-2000 is currently valid in decision-making and hydrological regime evaluation (Šipikalová, 2005). However, various changes of hydrological regime were described in recent studies (Pekárová et al, 2017;Fendeková et al, 2018;Ďurigová and Hlavčová, 2020;Halmová et al, 2022;Poórová et al, 2023). Establishment of a new reference period is a sensitive topic, as the hydrological design values based on this reference period, are a vital part of many decisionmaking processes (e.g., flood protection, hydrological drought management, water use permits, etc.).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several State Departments of Transportation (DOTs) in the U.S. have used the risk assessment tool HyRisk, incorporating available data of different lengths and periods in relation to hydrology, hydraulics, and structure [45]. In the current study, since the hydrological regimes are least affected by human activities, the adopted approach is also similar to the approach of using 'normal', 'quasi-periodicities', or 'potential' cycles for hydrologic analysis [46]. Quasi-periodicities or potential cycles imply specific periods for which the watersheds are least disturbed [46]; therefore, such periods can be different across watersheds.…”
Section: Selection Of Sitesmentioning
confidence: 99%
“…In the current study, since the hydrological regimes are least affected by human activities, the adopted approach is also similar to the approach of using 'normal', 'quasi-periodicities', or 'potential' cycles for hydrologic analysis [46]. Quasi-periodicities or potential cycles imply specific periods for which the watersheds are least disturbed [46]; therefore, such periods can be different across watersheds.…”
Section: Selection Of Sitesmentioning
confidence: 99%